Accounting ‐ “one of the finest inventions of the human spirit”* - CHAMBERS, R.J. (Contemporary Accounting Research, 1984)
Abstract. To commerce and to finance there can be great service given by accountancy. Its power, though, will not be fully known while bits and pieces stand apart, alone. To teach, to practise, to research, invent, is how the time of many has been spent. But cost of time and effort has been vain; for doubt, dispute, confusion still remain. A better prospect far there is in reach. If those who practise and research and teach were disciplined in such a way that each acknowledged that a common course of thought relates, for all men, to things sold and bought ‐ Accounting, then, might do the job it ought.